2014
DOI: 10.1074/jbc.m114.550111
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial Protein NLRX1 Controls the Balance between Extrinsic and Intrinsic Apoptosis

Abstract: Background: NLRX1 is a member of the Nod-like receptor family that localizes to the mitochondrial matrix and whose function remains poorly understood.Results: NLRX1 plays a key role in regulating apoptotic cell death and is important in the control of tumorigenesis.Conclusion: NLRX1 regulates the balance between extrinsic and intrinsic apoptosis in cancer cells.Significance: Targeting NLRX1 function could be an interesting strategy against cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 19 publications
8
54
0
Order By: Relevance
“…Recently, our lab has identified a role for NLRX1 in the control of apoptotic cell death sensitivity in transformed but not primary cells, suggesting a link between NLRX1 and tumorigenesis (259). In addition, our data reveal that NLRX1-deficient mice exhibit resistance to colorectal cancer in an AOM model but increased susceptibility to AOM/ DSS-induced carcinogenesis, which was associated with increased apoptosis induced by DSS.…”
Section: Cancersupporting
confidence: 51%
“…Recently, our lab has identified a role for NLRX1 in the control of apoptotic cell death sensitivity in transformed but not primary cells, suggesting a link between NLRX1 and tumorigenesis (259). In addition, our data reveal that NLRX1-deficient mice exhibit resistance to colorectal cancer in an AOM model but increased susceptibility to AOM/ DSS-induced carcinogenesis, which was associated with increased apoptosis induced by DSS.…”
Section: Cancersupporting
confidence: 51%
“…NLRX1 has been previously shown to negatively regulate NF-κB signaling and this attenuation is correlated with increased proliferation and tumorigenesis in cancer models (11, 29). Thus, we next profiled gene expression to evaluate NF-κB signaling following TBI in the Nlrx1 −/− and wild type brain following CCI injury.…”
Section: Resultsmentioning
confidence: 99%
“…These findings support the previous observations with rotenone and provide additional mechanistic insight into the in vivo loss of neurons observed in the Nlrx1 −/− mice following TBI. Several prior studies have evaluated the role of NLRX1 in cell death and proliferation in monocytes, fibroblasts, and epithelial cells (11, 19, 29, 63). Likewise, NLRX1 has also been shown to modulate ROS signaling and autophagy in these diverse cells following activation via pathogen associated molecular pattern stimulation and/or pathogen exposure (14, 16, 29, 64, 65).…”
Section: Discussionmentioning
confidence: 99%
“…A recent pair of studies have suggested that NLRX1 functions as a tumor suppressor through modulating apoptosis [16, 17]. In one study, NLRX1 expression was found to differentially regulate resistance to extrinsic and intrinsic apoptotic signals in transformed, but not primary murine embryonic fibroblasts [17]. In the other study, NLRX1 was found to function as a tumor suppressor by regulating TNF induced apoptosis in immortalized cell lines [16].…”
Section: Resultsmentioning
confidence: 99%